Against divided cities in Europe. - (:unkn) unknown (My University, 2013)
Dieses Papier wurde vom URBACT Arbeitskreis : "Against Divided cities in Europe" erstellt. Ziel des Arbeitskreises ist es, die existierenden Richtlinien zu räumlichen und sozialen Ungleichheiten in europäischen Städten zu überdenken.

This report was produced by the URBACT Workstream "Against Divided cities in Europe". The aim of the group is to help European cities to rethink existing policies concerning spatial and social segregation in urban areas.
Keywords: Stadtsoziologie; Stadtstruktur; Sozialräumliche Gliederung; Segregation; Stadtraum; Sozialpolitik; Sozialraum; Sozialsituation; Soziale Ungleichheit